LANGKAH STRATEGIS OPTIMALISASI SISTEM EKONOMI SYARIAH - Syarifah Gustiawati Mukri (SALAM: Jurnal Sosial dan Budaya Syar-i, 2014)
Abstract: Step Strategic Optimization of Islamic Economic System. The role of Islamic financial system in Indonesia has been shown to support the creation of higher economic development, and also support the establishment of a more stable financial system, to achieve the well-being of individuals and society. In order for the role to be significant, hence the need for a strategic steps in the effort to optimize the Islamic economic system. This is to accelerate the development of the Islamic financial system, both nationally and internationally. This article aims to review the philosophical system of Islamic banking. The systems and practices should be done in order to accelerate the pace of Islamic economic development in Indonesia. Keywords: Step Strategic, optimization, Islamic Economic System Abstrak: Langkah Strategis Optimalisasi Sistem Ekonomi Syariah. Peranan Sistem keuangan syariah di Indonesia telah dipercaya dapat mendukung terciptanya  pembangunan ekonomi yang lebih tinggi, dan juga menyokong terwujudnya sistem keuangan yang lebih stabil, untuk mencapai kesejahteraan individu dan masyarakat. Agar peranan tersebut dapat dirasakan lebih signifikan, maka perlu adanya langkah strategis dalam upaya optimalisasi sistem ekonomi syariah dalam rangka mempercepat perkembangan sistem keuangan syariah, baik secara nasional maupun  internasional. Tulisan ini bertujuan untuk mengkaji sistem ekonomi syariah secara filosofis, sistem dan praktik yang harus dilakukan dalam rangka mempercepat langkah perkembangan ekonomi syariah di Indonesia. Kata Kunci: Langkah Strategis, Optimalisasi, Sistem Ekonomi SyariahDOI: 10.15408/sjsbs.v1i1.1521